2018
DOI: 10.4103/ijpsym.ijpsym_374_17
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone Induced Thrombocytopenia: Is it a Signal of Drug Induced Myelosuppression?

Abstract: The U.S. Food and Drug Administration (FDA) has approved a supplemental new drug application Lurasidone (Latuda, Sunovion Pharmaceuticals), an atypical antipsychotic, for the treatment of schizophrenia in adolescents 13–17 years of age. Lurasidone was previously indicated in the U.S. for the treatment of adults with schizophrenia and major depressive episodes with bipolar I disorder as monotherapy. We present a case of a 29-year-old male patient who was hospitalized with thrombocytopenia (WHO grade-3 toxicity)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Authors have reported thrombocytopenia in a patient with bipolar depression who had received 80 mg/day of lurasidone for 2.5 months. [4] Few case reports also mentioned agranulocytosis as a dose-dependent adverse effect of lurasidone, which reverted after reducing the dose. [5] Anemia is rarely reported as an adverse effect; one study has observed the occurrence of anemia with the use of lurasidone during premarketing evaluation of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Authors have reported thrombocytopenia in a patient with bipolar depression who had received 80 mg/day of lurasidone for 2.5 months. [4] Few case reports also mentioned agranulocytosis as a dose-dependent adverse effect of lurasidone, which reverted after reducing the dose. [5] Anemia is rarely reported as an adverse effect; one study has observed the occurrence of anemia with the use of lurasidone during premarketing evaluation of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory tests showed hyperprolactinemia and thrombocytopenia – the level of platelets was 37 × 103/µl. Due to symptoms and test results, the patient was discontinued from lurasidone, and after a week, an improvement was observed in control tests – the platelets increased to 183 × 103/µl, and the patient’s clinical condition also improved [ 5 ]. Despite the fact that lurasidone is considered a very safe drug, in the literature you can find isolated descriptions of other, also non-hematological, side effects, e.g., the case of a 28-year-old patient who developed an oculogyric crisis after increasing the dose of the drug to 80 mg/d [ 6 ].…”
Section: Commentmentioning
confidence: 99%